“Introduction. Transnational Connections between Activists and the Global Cold War “East” (1960-1990” , in: Chris Saunders, Helder Adegar Fonseca and Lena Dallywater (eds), Southern African Liberation Movements and the Global Cold War “East”. Transnational Activism 1960-1990 [Coll. Dialectics of the Global Series] - Fonseca, Helder (2019)
This volume explores ways in which the liberation movements in Southern Africa were connected to people in the countries that were regarded as part of the `East’ in the Cold War decades of the 1960s, 1970s, and 1980s. The many different forms such connections took have been little investigated. The chapters that follow showcase studies of such interactions, at both leadership and grass-roots levels, seeking to explain why they took the form they did. Members of liberation movements not only worked together in exile headquarters but travelled to Eastern Europe and elsewhere for military and political training or to receive vocational, secondary and university education. Little is known about the networks that were shaped through the movement of individuals and ideas. In the studies included here such connections are teased out. This Introduction attempts to bring some of the threads together and provide general context.